A strategy for assessing acute (transient) pain or discomfort in the strength and conditioning environment - Meir, R.; Chapman, N.; Whitting, J. W.; Crowley-McHattan, Z. J. (Strength and Conditioning Journal, 2019)
Experiencing acute (transient) pain and discomfort can be a characteristic of exercise and sport participation. In this context, acute pain or discomfort can be experienced by injured and injury-free athletes alike. Acute pain or discomfort in the strength and conditioning (S&C) environment can be experienced during particular movements or exercises. This may be the result of poor exercise technique and/or soft-tissue dysfunction. This article proposes a possible strategy, which can be used by the S&C coach, to modify training based on the acute (transient) pain or discomfort experienced by athletes during training.